Analisis Penggunaan Bahasa pada Film Ayat-Ayat Cinta 1 - Nurul Fawzani; Sulfikar; Amran AR (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2023)
The film Ayat-ayat Cinta is one of Indonesia's best-selling films with a religious genre that conveys messages of peace, love, and the meaning of friendship that upholds humanist values ​​and religious values. The film shows the use of heterogeneous language because it tells the life of an Indonesian student who is studying in Egypt. So this study aims to describe the form of code-switching and code-mixing contained in the film Ayat-Ayat Cinta 1. This study uses qualitative research methods. The data source of this research is the film Ayat-Ayat Cinta 1. The data collection uses the technique of listening to the narrative of the characters in the film and then analyzing using a descriptive method. The form of code-switching found in the film Ayat-Ayat Cinta 1 is the form of external code-switching which includes: code-switching from Indonesian to Arabic, and code-switching from Arabic to Indonesian. While the forms of code mixing found in this film are in the form of word insertion code-mixing, clause insertion code-mixing, and idiom insertion code-mixing. The factors causing code switching and code mixing in this film are caused by the speaker and the interlocutor, the situation, the background of the speaker, and the subject of the conversation.